Pengaruh Terapi Benson terhadap Tekanan Darah pada Lansia dengan Hipertensi: The Impact of Benson Therapy on Blood Pressure Among Elderly Individuals with Hypertension - Sumiarti; Probo Wijayanto, Wisnu; Hernanda, Rice; Sutrisno (Journal of Nursing Education and Practice, 2024)
Introduction: One of the most common degenerative diseases suffered by the elderly is hypertension. About 26.4% of people worldwide have hypertension, and an estimated 9.4 million die from hypertension.  The prevalence in Indonesia is 34.11% and the highest in South Kalimantan is 44.33% for Lampung province with a total of 2,175,791 cases and in Central Lampung 303,958 cases. The risk of hypertension increases with age, the incidence rate at the age of 55-64 years is 45.9%, 65-74 years is 57.6% and 63.8% above 75. One non-pharmacological way is to use Benson therapy. Objectives: The purpose of this study was to determine the effect of Benson Therapy on Blood Pressure in the Elderly with Hypertension in the UPTD Simbarwaringin Puskesmas Working Area in 2024. Method: This study is a pre experiment analytic study with a two group pretest posttest design. Sample size of 34 consisting of 17 elderly people for each group taken by purposive sampling. Data collection with digital tension meter, data analysis using independent t test. Result: The results showed that the characteristics of elderly patients with hypertension were mostly aged 60-65 years (58.8%), female gender (82.4%), elementary school education (50%) and not working (91.2%). The mean pretest blood pressure of the control group was 162.3, while that of the intervention group was 165.6 mmHg. The mean posttest blood pressure of the control group was 63.8 while the intervention group was 149 mmHg. There is an effect of benson therapy on blood pressure in the elderly with hypertension with a p value: 0.000. Conclution: There is an effect of benson therapy on blood pressure in the elderly with hypertension.